2014
DOI: 10.1177/1534650114548313
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Single Case Controlled Study of The Optimum Performance Program in Sports in a Collegiate Athlete

Abstract: In this study, a sport-specific adaptation of Family Behavior Therapy (i.e., The Optimum Performance Program in Sports [TOPPS]) in a collegiate athlete was examined, including a controlled evaluation of several of its intervention components utilizing multiple-baseline methodology. After a 3-week baseline consisting of program orientation, cultural enlightenment, and goal development was established for unsafe sexual practices, alcohol binge drinking (four or more drinks per occasion), and teammate relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The Optimum Performance Program in Sports (TOPPS) is an evidence-based program that was adapted from Family Behavior Therapy (FBT; Azrin et al, 1994). In both uncontrolled and controlled case trials, TOPPS has preliminarily demonstrated concurrent improvements in mental health and sport performance in collegiate athletes (Chow et al, 2015; Donohue et al, 2015; Pitts et al, 2015), and outcomes are currently being examined in a large-scale randomized controlled trial in collegiate athletes (National Institute on Drug Abuse [NIDA]; 1 R01 DA031828).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…The Optimum Performance Program in Sports (TOPPS) is an evidence-based program that was adapted from Family Behavior Therapy (FBT; Azrin et al, 1994). In both uncontrolled and controlled case trials, TOPPS has preliminarily demonstrated concurrent improvements in mental health and sport performance in collegiate athletes (Chow et al, 2015; Donohue et al, 2015; Pitts et al, 2015), and outcomes are currently being examined in a large-scale randomized controlled trial in collegiate athletes (National Institute on Drug Abuse [NIDA]; 1 R01 DA031828).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Family Behavior Therapy (FBT) is reported by experts to be a promising intervention for drug abuse and coexisting symptomology (e.g., Austin et al, 2005;Bender et al, 2006;Carroll & Onken, 2005;Henggeler, 2015;Landers et al, 2018;National Academies of Sciences, Engineering, and Medicine, 2016). This intervention was originated from the Community Reinforcement Approach (Azrin et al, 1982) and has demonstrated efficacy in both controlled (Azrin et al, 1996;Azrin, McMahon, et al, 1994;Chow et al, 2015, Donohue et al, 2014 and uncontrolled clinical trials (e.g. Donohue et al, 2010;Galante et al, in press;Gavrilova et al, 2017;LaPota et al, 2011;Plant & Holland, 2018;Romero et al, 2010).…”
Section: Consideration Of Consumer Intervention Preferencesmentioning
confidence: 99%
“…; Azrin & Holz, 1966; Azrin, McMahon, et al, 1994; Azrin & Nunn, 1973; Azrin, Nunn, & Frantz, 1980), and were subsequently embedded within the Community Reinforcement Approach (Azrin, Sisson, Meyers, & Godley, 1982; Meyers & Smith, 1995), Motivational Interviewing (MI; Miller & Rollnick, 2013), and Family Behavior Therapy (FBT; Azrin, Donohue, Besalel, Kogan, & Acierno, 1994). These evidence-based therapeutic interventions incorporate consequence reviews to enhance client motivation in improving undesired habits, reducing problem behaviors, increasing prosocial and healthy behaviors, and achieving goals (Azrin, Donohue, et al, 1994, Azrin et al, 2001; Azrin, McMahon, et al, 1994; Chow et al, 2015; Donohue & Azrin, 2011; Donohue et al, 2015; Hettema, Steele, & Miller, 2005; Meyers & Smith, 1995; Miller & Rollnick, 2013).…”
Section: Review Of Negative and Positive Consequencesmentioning
confidence: 99%